Digital Transformation in Rural Governance: A Case Study of E-Government Implementation in Sukamakmur Village, Bogor - Hutauruk, Rosinta Paulina; Juantara, Bendi; Fahmi, Ade (Universitas Sang Bumi Ruwa Jurai, 2021)
This study explores the digital transformation process in village governance in Indonesia, focusing on the implementation of e-government systems to improve public services, transparency, and administrative efficiency. Using a qualitative case study in Sukamakmur Village, Bogor Regency, the research investigates enabling factors, challenges, and impacts of digitizing village administration. The findings indicate that while digital adoption has enhanced service delivery and citizen engagement, it also faces barriers such as limited infrastructure, digital literacy gaps, and institutional inertia. Recommendations are offered for scaling digital transformation across rural governance contexts.